Analysis of mechanical properties of fly ash and boiler slag integrated geopolymer composites - Ahmed Chowdhury, Jasim; Shahidul Islam, Md; Ashraful Islam, Md; Abdullah Al Bari, Md; Kumar Debnath, Arup (Sustainable structures, 2025)
This study explores sustainable alternatives to conventional raw materials in composite manufacturing by integrating fly ash (FA) and boiler slag (BS) into geopolymer composites. FA and BS were combined with alkali activators (AA) to evaluate their mechanical and physical properties under varying compositions and curing conditions. From bottom ash, only the boiler slag portion was selected for use in this study, which was ground to 300µm particle size. The research examined the effects of BS content (25%, 50%, and 75%), solid-to-liquid ratios (0.5, 1.0, 1.5, and 2.0), AA ratios (Na₂SiO₃/NaOH: 1.0 to 2.5), and curing temperatures (60°C to 90°C) on the compression strength of the composites. Results showed that composites with 25% BS and an AA ratio of 1.5 achieved the highest compressive strength (30.38 MPa) after 7 days of curing. Apparent porosity and water absorption decreased with increasing BS content, while optimal curing temperatures ranged from 70°C to 80°C. At elevated temperatures, compressive strength declined due to thermal degradation, but composites maintained the performance comparable to conventional materials. SEM analysis revealed a geopolymer matrix with dense microstructures. These findings demonstrate that incorporating BS and FA into composite manufacturing provides a viable eco-friendly alternative to traditional materials, reducing reliance on geo-sand and cement while enhancing sustainability.